Analisis Hubungan Pola Asuh Orang Tua dengan Perkembangan Kognitif Siswa Kelas V SDN Karangtempel Semarang - Mira Maharani; Veryliana Purnamasari; Wawan Priyanto (STKIP Andi Matappa Pangkep, 2021)
The application of various parenting affects the cognitive development of different students in one class, this can be seen from the learning outcomes of children at school. Based on this, the researchers analyzed the relationship between parenting and students' cognitive development. The purpose of this study was to determine the relationship between parenting applied by parents and the cognitive development of fifth graders. This type of research was qualitative. There are three stages of data analysis, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. The research was conducted at Karangtempel State Elementary School, Semarang. The results of the parenting questionnaire showed that nine parents tended to apply authoritarian parenting and seven parents tended to apply authoritative parenting. The results showed that the cognitive development of students with the application of authoritarian parenting tended to increase and decrease unstable, and the cognitive development of students with the application of authoritative parenting experienced continuous improvement. It was concluded that there was a relationship between parenting and students’ cognitive development.